Deferiprone effectiveness in thalassemia major children with or without hepatitis B or C virus infection: a non-randomized study - Yovita Ananta; Pustika Amalia Wahidiyat; Hanifah Oswari (Paediatrica Indonesiana, 2010)
Background A high incidence rate of hepatitis B or C virusinfection is found among thalassemia children in Indonesia. Thismay influence deferiprone effectiveness.Objective To determine the effectiveness of deferiprone inthalassemia children with or without hepatitis B or C virusinfection.Methods A non-randomized clinical study was performed atThalassemia Center Jakarta. Subjects were thalassemia childrenwith serum ferritin level > 1000 ng/mL who had hepatitis B orC virus infection. A match control pair was recruited based onsimilar duration of transfusion therapy, thalassemia type, andinitial serum ferritin level. All subjects received initial deferipronedose of 50 mg/kg/day for 3 months. Those whose ferritin decreased2:: 10% continued to receive deferiprone of 50 mg/kg/day for thefollowing 3 months. Otherwise, deferiprone dose was adjustedto 75 mg/kg/day.Results Forty-eight subjects were recruited. After 3 months oftreatment, 16/24 subjects without and 6/24 subjects with hepatitisB or C had their ferritin level decreased 2:: 10%. Mean ferritinserum level of all subjects after 6 months was significantly reducedfrom 4734 (SD 2116) to 3695 (SD 1709) ng/mL. Lower meandeferiprone dose, lower mean post- study ferritin serum level andhigher mean percentage of ferritin serum level decrement werefound in subjects without hepatitis B or C infection than thosewith infection.Conclusions Deferiprone 50-7 5 mg/kg/day for 6 months is effectivein reducing serum ferritin level of thalassemia major children; itis more effective in thalassemia children without hepatitis B or Cvirus infection.